A conceptual model for ethics committees: preliminary sociological syntheses - Cadenas, Hugo (Acta Bioethica, 2019)
The text proposes an initial conceptual approach to empirical sociological research on ethics committees, which is understood as a currently underdeveloped field of study. The model aims to support qualitative, quantitative or mixed researches on the subject based on a set of dimensions and concepts selected from the most important works of sociologists Émile Durkheim, Max Weber, Talcott Parsons, Jürgen Habermas and Niklas Luhmann. The text concludes with a preliminary sociological definition for the ethics committees and also methodological suggestions for empirical research.